Garcinia: A genus of nutraceutical fruits - Tripathi, Prakash Chandra (Indian Horticulture, 2022)
Genus Garcinia is one of the important genus of fruiting plants belonging to the family Clusiaceae and includes about 200 species found in tropical Asia and Africa. Thirty five species of Garcinia are found in India. Out of these, 17 species are endemic. Of these, seven are endemic to the Western Ghats, six in the Andaman and Nicobar Islands and four in the northeastern region of India. Several species of this genus have traditionally been used by the natives of Asia and Africa in their day to day lives.